OP0284 Evaluation of the impact of baseline levels of MRI-detected inflammation on treatment response in early, seropositive, MTX-NAÏVE RA: data from the avert trial. (15th June 2017) - Ahmad, H; Baker, J; Østergaard, M; Emery, P; Durez, P; Ye, J; Banerjee, S; Conaghan, P
Abstract : Background: AVERT (Assessing Very Early Rheumatoid arthritis Treatment) was a Phase IIIb, randomized, 24-month (M) trial with a 12M, double-blind treatment period, and included contrast-enhanced MRI of the dominant hand and wrist. MRI can provide direct evidence of joint inflammation, enabling stratification of patient (pt) data according to MRI inflammation level, e.g. low vs high. 1 This stratification is hypothesized to predict clinical treatment response. Objectives: To evaluate the proportion of pts achieving remission at M12 by baseline (BL) MRI-detected inflammation status and treatment group. Methods: In AVERT, pts with early RA received abatacept (ABA) + MTX, ABA monotherapy or MTX. MRI inflammation was scored by two central readers at BL and M12. In this post hoc analysis, pts were stratified into "low" and "high" BL MRI inflammation groups. Low: ≤3 for synovitis, ≤3 for osteitis and ≤9 when combined (osteitis double weighted); 2 high: >3, >3 or >9, respectively. The proportion of pts achieving CDAI (≤2.8), DAS28 (CRP; <2.6), SDAI (≤3.3) and Boolean (TJC ≤1, SJC ≤1, CRP ≤1 mg/dL and pt global assessment of disease activity ≤1 [0–10 cm scale]) remission at M12 was compared by BL MRI inflammation and treatment group. Results: Of 351 pts randomized and treated, 337 (96.0%) had MRI data at BL (ABA + MTX, n=114; ABA monotherapy, n=112; MTX, n=111). Mean (SD) BL synovitis, osteitis and total scores, respectively, for pts with low MRI inflammation receiving ABA + MTX vs MTX alone were: 2.6 (2.0) vs 3.1 (2.4), 0.3 (0.6) vs 0.2 (0.5) and 3.1 (2.4) vs 3.5 (2.7); high MRI inflammation: 9.2 (3.6) vs 9.3 (3.6), 10.0 (9.7) vs 10.7 (9.8) and 29.3 (21.3) vs 30.7 (21.3). BL DAS28 (CRP), CDAI and SDAI scores, respectively, for pts with low MRI inflammation receiving ABA + MTX vs MTX alone were: 5.1 (1.1) vs 5.0 (1.3), 34.0 (14.7) vs 32.1 (15.0) and 39.9 (17.4) vs 43.5 (24.6); high MRI inflammation: 6.2 (1.2) vs 5.6 (1.4), 43.4 (16.2) vs 37.7 (18.1) and 76.9 (44.9) vs 61.1 (35.2). The proportion of pts with low BL MRI inflammation attaining remission at M12 was similar regardless of treatment. In pts with high MRI inflammation, remission rates were significantly greater in pts treated with ABA + MTX vs MTX alone (Table). Conclusions: Pts with higher MRI inflammation may derive greater benefit from abatacept + MTX vs MTX alone. BL MRI inflammation is a predictor of subsequent clinical treatment response to abatacept in RA. MRI may have clinical utility in treatment decisions beyond information obtained from clinical assessments alone. References: Gandjbakhch F, et al. J Rheumatol 2014;41:398–406. Ahmad HA, et al. Ann Rheum Dis 2016;75:624. Disclosure of Interest: H. Ahmad Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Baker: None declared, M. Østergaard Grant/research support from: AbbVie, Bristol-Myers Squibb, Janssen, Merck, Speakers bureau: AbbVie, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Centocor, GSK, Hospira, Janssen, Merck, Mundipharma, Novartis, Novo Nordisk, Orion, Pfizer, Regeneron, Schering-Plough, Roche, Takeda, UCB, Wyeth, P. Emery Grant/research support from: AbbVie, Merck, Pfizer, Roche, Consultant for: AbbVie, Bristol-Myers Squibb, Merck, Pfizer, Roche, Lilly, Novartis, Samsung Bioepis, P. Durez Speakers bureau: Bristol-Myers Squibb, Lilly, Janssen, Sanofi, Roche, Pfizer, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, P. Conaghan Grant/research support from: Bristol-Myers Squibb, Consultant for: AbbVie, Lilly, Novartis, Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Roche